Discrimination of Anopheles species of the Arribalzagia Series in Colombia using a multilocus approach (2018)
The Arribalzagia Series of the Anopheles Subgenus comprises morphologically similar species or members of species complexes which makes correct species identification difficult. Therefore, the aim of this work was to discriminate the morphospecies of the Arribalzagia Series present in Colombia using a multilocus approach based on ITS2, COI and CAD sequences. Specimens of the Arribalzagia Series collected at 32 localities in nine departments were allocated to seven species. Individual and concatenated Bayesian analyses showed high support for each of the species and reinforced the previous report of the Apicimacula species Complex with distribution in the Pacific Coast and northwestern Colombia. In addition, a new molecular operational taxonomic unit-MOTU was identified, herein denominated near Anopheles peryassui, providing support for the existence of a Peryassui species Complex. Further, the CAD gene, just recently used for Anopheles taxonomy and phylogeny, demonstrated its power in resolving phylogenetic relationships among species of the Arribalzagia Series. The divergence times for these species correspond to the early Pliocene and the Miocene. Considering the epidemiological importance of some species of the Series and their co-occurrence in malaria endemic regions of Colombia, their discrimination constitutes an important step for vector incrimination and control in the country.